Molding the Future: The Integral Role of Leadership Styles in Shaping Organizational Success - Ain Najihah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research provides a comprehensive examination of various leadership styles and their impact on organizational success. The study delves into the characteristics and effects of transformational, transactional, autocratic, democratic, authentic, spiritual, knowledge-oriented, and leadership commitment styles on key organizational outcomes such as employee satisfaction, innovation, and financial performance. Transformational leadership is highlighted for its ability to inspire and engage employees, fostering an environment conducive to innovation and adaptability. Transactional leadership, while effective in stable and predictable environments, shows limitations in dynamic settings requiring creativity. Autocratic leadership, often associated with diminished employee morale, contrasts with democratic leadership, which promotes employee participation and satisfaction. Authentic leadership emerges as a significant contributor to a positive organizational climate, emphasizing ethical behavior and trust. Spiritual leadership is recognized for aligning personal and organizational values, enhancing job satisfaction and organizational commitment. Knowledge-oriented leadership is identified as crucial in technology-driven sectors for fostering innovation and managing complex information flows. Leadership commitment is emphasized for its role in driving organizational change and performance. The study concludes that effective leadership requires adaptability and contextual awareness, with no single style being universally effective. The findings suggest that a blend of leadership styles, tailored to specific organizational contexts, can lead to enhanced organizational performance and success. This research contributes to the field of organizational behavior by providing insights into the effective application of diverse leadership styles in varying organizational contexts.